ChemInform Abstract: A Noble‐Metal‐Free, Tetra‐Nickel Polyoxotungstate Catalyst for Efficient Photocatalytic Hydrogen Evolution. Issue 8 (February 2015) - Lv, Hongjin; Guo, Weiwei; Wu, Kaifeng; Chen, Zheyuan; Bacsa, John; Musaev, Djamaladdin G.; Geletii, Yurii V.; Lauinger, Sarah M.; Lian, Tianquan; Hill, Craig L.
Abstract Na6K4 [Ni4(H2O)2 (PW9O34)2]·32H2O is synthesized by refluxing an aqueous solution of Na2WO4, Na2HPO4, and Ni(OAc)2 for 2.5 h, followed by addition of KOAc (73% yield).